Mimosa diversiplla var. subglabriseta (MimosoIdeae, Leguminosae), a new record for the flora of Paraguay - Luna, Javier A. (2012)
The presence of Mimosa diversipila M. Micheli var. subglabriseta Barneby & Fortunato is now reported for first time in Paraguay. A revision of Barneby's initial description of the variety and photographs of one of the Paraguayan specimens are given in this paper.